Active learning and outreach activities into production engineering courses at UNIVASF/Campus Salgueiro - Oliveira-Melo, Felipe Guilherme; Sant'Anna, Ângelo Márcio Oliveira; Barbosa, Ava Santana (Brazilian Journal of Production Engineering, 2025)
This paper presents and discusses the perception of students enrolled in the “Quality Management” and “Service Management” courses offered in the Industrial Engineering undergraduate program at the Federal University of São Francisco, Campus Salgueiro. These courses were based on active learning methodologies and outreach activities. A survey was administered to 20 students who responded to an evaluation form provided virtually. The results indicate a generally positive perception of the courses’ dynamism and the development of professional skills. The pedagogical approach based on active teaching-learning methods was positively evaluated by the students. The findings highlight the importance of the teacher’s role as a facilitator in the learning process, promoting an engaging and formative educational environment. The study has significant implications for teaching practices and the curricular development of engineering programs, providing insights for improvements in the teaching and learning process.